Upaya Penegakan Hukum Tindak Pidana Pemerasan Yang Dilakukan Dengan Modus Iuran Keamanan Di Pasar Mardika - Mansur, Sahrul; Lewerissa, Yanti Amelia (SANISA: Jurnal Kreativitas Mahasiswa Hukum, 2026)
Introduction: Extortion, often disguised as security fees, is a pervasive legal issue, particularly at Mardika Market in Ambon City. This practice is carried out by certain individuals, claiming to provide security, but is accompanied by elements of coercion, threats, and violence, harming traders and creating a sense of insecurity. This situation indicates that law enforcement against this practice has not been optimal.Purposes of the Research: This study aims to analyze law enforcement efforts against the crime of extortion using the security fee method and to identify the obstacles faced by law enforcement officers in eradicating it.Methods of the Research: The research method used was empirical legal research with a qualitative approach. Data was obtained through interviews with relevant parties, direct observation at the research location, and literature review. The collected data was then analyzed descriptively and qualitatively.Results / Findings / Novelty of the Research: The research results show that extortion practices involving security fees are still common and tend to be organized. Law enforcement efforts have been implemented through preventive and repressive measures, but they have not been optimal. Obstacles include low public legal awareness, victims' fear of reporting, limited facilities and infrastructure, and a lack of coordination among law enforcement officials. Therefore, firmer and more comprehensive law enforcement and increased public legal awareness are needed to create a safe and orderly market environment.